The Petroglyphs of Palpa: Rupestrian art from the Formative Period on the South Coast of Peru - Isla, Johny (2023)
This article presents the study of a group of petroglyphs from the Formative period of the Palpa valleys, linked to the Paracas period (800-200 BC) and with the period of transition from Paracas to Nasca, known as Proto Nasca (200-1 BC). Likewise, the results of a study that focuses on aspects related to their location, typology, chronology and function are presented, as well as the meaning they had in the cultural process of the region.